Odpowiedź:
1.
a)
4(x+3)=−22
4x + 12 = -22
4x = -22 - 12 /:4
x = -34/12 = -2 10/12 = -2 5/6
b)
5(x+12)=−60
5x + 60 = -60
5x = -60 - 60 /:5
x = -120/5 = -24
c)
10(x+5)+8 = 88
10x + 50 + 8 = 88
10x = 88 - 58 /:10
x = 30/10 = 3
d)
1x + 17 = 13
x = 13 - 17 = -4
e)
6(x+14)+15 = 69
6x + 84 + 15 = 69
6x = 69 - 99 /:6
x = 30/6 = 5
f)
7(x+16)-13 = 162
7x + 112 - 13 = 162
7x = 162 - 99 /:7
x = 63/7 = 9
g)
1(x+17) + 18 = 28
x + 17 + 18 = 28
x = 28 - 35 = -7
h)
1x+4 = -1
x = -1 - 4 = -5
i)
10(x+2) = -50
10x + 20 = -50
10x = -50 - 20 /:10
x = -70/10 = -7
j)
9x + 6 = -30
9x = -30 - 6 /:9
x = -36/9 = -4
Szczegółowe wyjaśnienie: